Intermediate-depth core drilling at Mizuho Station, Antarctica by JARE-25 (abstract) - Kawada, Kunio; Fujii, Yoshiyuki; Yoshida, Minoru; Matsumoto, Shin'ichi; Narita, Hideki (1986)
P(論文) departmental bulletin paper